Cover Picture: Dissecting Ubiquitin Signaling with Linkage‐Defined and Protease Resistant Ubiquitin Chains (Angew. Chem. Int. Ed. 47/2014). Issue 47 (26th September 2014) - Schneider, Tatjana; Schneider, Daniel; Rösner, Daniel; Malhotra, Saurav; Mortensen, Franziska; Mayer, Thomas U.; Scheffner, Martin; Marx, Andreas
<x xml:space="preserve">Abstract</x> The fate of poly‐ubiquitylated proteins is determined by the linkage type of the ubiquitin chains attached. In their Communication on page 12925 ff., T. U. Mayer, M. Scheffner, A. Marx et al. report a straightforward method that relies on codon expansion and bioorthogonal polymerization to generate linkage‐defined and protease‐resistant ubiquitin chains. These chains can be used to analyze ubiquitin signaling in cell extracts, as demonstrated by a study of linkage‐dependent effects on cell‐cycle progression.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>